An exploration of learners' experiences of bullying as an act that promotes exclusion in a high school in Botha-Bothe district, Lesotho - Lekena, Mots'elisi Anacletta (My University, 2016)
This study explored learners’ experiences of bullying and how it makes them feel excluded in a school in Botha-Bothe district, Lesotho. A qualitative research method was applied, which included analysis of data obtained from narrative essays and from individual, semi-structured interviews. A narrative essay question was given to 76 Grade eight learners who participated in this study to write about their experiences of bullying and how it makes them feel. Out of these 76 Grade eight learners who wrote narrative essays, a purposive sampling was used to select 6 learners who seemed to experience multiple forms of bullying to participate in individual, semi-structured interviews. Various forms of bullying, the effects and factors that contribute to bullying which make learners feel excluded in a school environment are described. The study explicates that learners were exposed to multiple forms of bullying, for example, physical and verbal bullying. In addition, it was established that bullying exhibits psychological and emotional effects, particularly on the victims. Unique to this study were participants’ perceived reasons why they think they are vulnerable to bullying and what they think triggers some learners to bully others. The study was brought to a conclusive end by highlighting the need for a systematic way of assessing and addressing the problem of bullying in schools. The study also highlighted that parental involvement is as crucial in dealing with cases of bullying as it is presumably caused by the way in which children are raised from their homes.
Submitted in partial fulfilment of the requirements for degree of Master of Education in the Faculty of Humanities at the University of the Witwatersrand
Keywords: Bullying in schools--Lesotho; School violence--Lesotho; Education (Secondary)--Lesotho